EGGSN for Mobile Internet - Xun Dong; Jiyan Wang; Liang Li; Zhi Zheng; Hua Ren (Dianxin kexue)
In response to the new challenges brought by mobile internet, mobile core network needs to introduce enhanced technology. Based on the research on enhanced technology, the core network solution for mobile internet was proposed, called EGGSN. Then the architecture and technical scheme of EGGSN was introduced. Finally, the advantages and disadvantages of EGGSN networking were analyzed.